2005
DOI: 10.1007/s10789-005-0292-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Ion Mobility, and Superionic Conductivity of (1 − x)PbF2 ⋅ xMF n (M = Li, Na, K, Rb, Cs, Zr) Solid Solutions

Abstract: Ionic motion and conduction in (1 -x )PbF 2 · x ZrF 4 and (1 -x )PbF 2 · x MF (M = alkali-metal cation) solid solutions are studied by 19 F and 207 Pb NMR and impedance spectroscopy. The factors determining ionic motion in the solid solutions and their structure and energetics in the range 170-550 K are analyzed. The ionic conductivity of (1 − x )PbF 2 · x ZrF 4 with x ≤ 0.4 and 0.93PbF 2 · 0.07MF is shown to be 10 -4 to 10 -2 S/cm at temperatures above 425 K, which places these materials among superionics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…13 Fluoride-ion conductors exhibiting high conductivity in a wide temperature range are essential to achieve ASSFIBs with high power densities and wide operating temperature ranges. Various crystal structures are known for uoride-ion conductors, such as uorite-type MSnF 4 (M = Pb, Ba) 14,15 and Pb 1−x M x F 2±d (M = K, Zr), 16,17 perovskite-type APbF 3 (A = Cs, Rb), 9,18 and ASn 2 F 5 -type compounds (A = Na-Cs, Tl, and NH 4 ). 19 Ternary tin uorides with open space in their structures, such as PbSnF 4 and ASn 2 F 5 , exhibit high uoride-ion conductivities above 10 −4 S cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…13 Fluoride-ion conductors exhibiting high conductivity in a wide temperature range are essential to achieve ASSFIBs with high power densities and wide operating temperature ranges. Various crystal structures are known for uoride-ion conductors, such as uorite-type MSnF 4 (M = Pb, Ba) 14,15 and Pb 1−x M x F 2±d (M = K, Zr), 16,17 perovskite-type APbF 3 (A = Cs, Rb), 9,18 and ASn 2 F 5 -type compounds (A = Na-Cs, Tl, and NH 4 ). 19 Ternary tin uorides with open space in their structures, such as PbSnF 4 and ASn 2 F 5 , exhibit high uoride-ion conductivities above 10 −4 S cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…To obtain high capacities during both charging and discharging, high ionic and electronic conductivities are required for the active material. The PbF2-based compounds exhibit fluoride ion conductivity [18][19][20][21]; therefore, PbF2 was selected as an active material for the fluoride shuttle battery (FSB). It has been reported that the high adhesion state with carbon improved the charge and discharge capacities of metal fluorides for the active materials of LIBs due to the increased electronic conductivity [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%